Determinants of Repurchase Intention Mediated by Customer Satisfaction Among “X” Coffee Application Users - Tjandra, Sabrina Layman; Rodhiah (Journal of Social Science and Business Studies, 2025)
This research aims to analyze and ascertain how repurchase intention among users of the "X" Coffee application is influenced by perceived ease of use, perceived usefulness and customer experience and mediated by customer satisfaction. The sample method is purposive sampling. The sample in this research consisted of “X” Coffee customers who have purchased “X” Coffee at least 5 times in the last 2 years using the “X” Coffee application and located DKI Jakarta. A Google Forms survey was used to get 235 respondents in total. With the assistance of SmartPLS 4.0, the data was processed using structural equation modeling (SEM). The outcomes show that perceived ease of use, perceived usefulness, customer experience, and customer satisfaction collectively have a positive and significant impact on repurchase intention. Repurchase intention is significantly and positively affected by perceived ease of use, positively and significantly impacted by perceived usefulness, positively and significantly impacted by customer satisfaction, and not significantly impacted by customer experience through customer satisfaction.